How do we change practice? - John Kestle (Brazilian Society for Pediatric Neurosurgery, 2021)
OBJECT: The goal of this video lecture was to show the importance to research group organizing protocols to reduce cerebrospinal fluid (CSF) shunt infection at Hydrocephalus Clinical Research Network (HCRN) centers (from 8.7% to 5.7%). Antibiotic-impregnated catheters (AICs) were not part of the protocol but were used off protocol by some surgeons. The authors therefore began using a new protocol that included AICs in an effort to reduce the infection rate further. The improvement of quality was related to reduce variation and improve outcome. METHODS The previous protocol was implemented at HCRN centers on January 1, 2012, for all shunt procedures (excluding external ventricular drains [EVDs], ventricular reservoirs, and subgaleal shunts). Compliance with the protocol and outcome events up to March 30, 2014, were recorded. The actual protocol is based on 7 points (HCRNq centers): intravenous antibiotics, skin preparation, hand scrub, double gloves, iodophoretic surgical field, catheter and antibiotics, and vancomycin irrigation RESULTS. Before protocol implementation in 30 participating centers, and 1318 subjects (1571 surgical cases) enrolled the overall infection rate was 6.0% (95% CI 5.1%-7.2%). The actual infection rate when using this new protocol has been analyzed. CONCLUSIONS CSF shunt procedures performed in compliance with a new infection prevention protocol at HCRNq centers had a lower infection rate than noncompliant procedures. Based on the current data, HCRNq centers the role of AICs compared with other infection prevention measures is still under analysis.